Respiratory cycle entrainment of septal neurons mediates the fast coupling of sniffing rate and hippocampal theta rhythm. - REILLY, RICHARD; O'MARA, SHANE (My University, 2014)
Memory for odour information may result from temporal coupling between the olfactory and hippocampal systems. Respiration defines the frequency of olfactory perception, but how the respiratory rate affects hippocampal oscillations remains poorly under- stood. The afferent connectivity of the medial septum/diagonal band of Broca complex (MS/DB) proposes this region as a cross- roads between respiratory and limbic pathways. Here we investigate if the firing rates of septal neurons integrate respiratory rate signals. We demonstrate that approximately 50% of MS/DB neurons are temporally correlated with sniffing frequency. Moreover, a group of slow-spiking septal neurons are phase-locked to the sniffing cycle. We show that inter-burst intervals of MS/DB theta cells relate to the sniff rate. Intranasal odour infusion evokes sniff phase preference for the activity of fast-spiking MS/DB neurons. Concurrently, the infusion augments the correlation between sniffing and limbic theta oscillations. During periods of sniffing – theta correlation, CA1 place cells fired preferentially during the inhalation phase, suggesting the theta cycle as a coherent time frame for central olfactory processing. Furthermore, injection of the GABAergic agonist muscimol into medial septum induces a parallel decrease of sniffing and theta frequencies. Our findings provide experimental evidence that MS/DB does not merely generate theta rhythm, but actively integrates sensorimotor stimuli that reflect sniffing rate. Such integration may provide temporal oscilla- tory synchronisation of MS/DB-innervated limbic structures with the sniffing cycle.
PUBLISHED
Keywords: odour information; odour information; Ageing; Neuroscience; Next Generation Medical Devices